Pengaruh Social E-Wom Dan Price Terhadap Purchase Intention Dengan Brand Trust Sebagai Variabel Mediasi - Devira Mezza Herawati; Imronudin Imronudin (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
The purpose of this study is to analyze the effect of Social E-Wom and Price on Purchase Intention with Brand Trust as a mediating variable. The research method used in this research is to use a quantitative model. The type of data used in the study is primary data. The population used in this study were all active users who have Shopee media. The sampling technique used is purposive sampling. The technique for determining the number of samples can use the Malhotra Formula. The number of samples for this study were 100 respondents. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS).The results of data analysis show that Social E-WOM has an insignificant effect on Purchase Intention. Price has a positive and significant influence on Purchase Intention. Social E-WOM has a positive and significant influence on Brand Trust. Price has a positive and significant influence on Brand Trust so that. Brand Trust has a positive and significant influence on Purchase Intention. Social E-WOM has a positive and significant influence on Purchase Intention through Brand Trust so that the sixth hypothesis is accepted. Price has a positive and significant influence on Purchase Intention through Brand Trust.